ISLAMISASI INTEGRASI INTERKONEKSI ILMU PENGETAHUAN DAN AGAMA ISLAM: MODEL KEILMUAN DI PERGURUAN TINGGI ISLAM - Hidayah, Ulil; Tobroni; Faridi (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2023)
This article discusses the concept of a scientific philosophical framework built by Islamic universities that switched form from IAIN to UIN. The object of this research is to compare three Islamic universities that already have the concept of scientific building of Islam and science, namely, UIN Maulana Malik Ibrahim Malang, UIN Sunan Ampel Surabaya, and UIN Sunan Kalijaga Yogyakarta. This research method uses descriptive qualitative by obtaining data from scientific literature and campus media sources as the object of research. The results of the study explain that the three UIN campuses in the study have similar scientific ontology sourced from al Quran and al Hadith, while in the epistemological aspect the scientific concept of UIN Malang is Islamization, the scientific concept of UIN Surabaya is integration and the scientific model of UIN Yogyakarta is Interconnection. And at the level of axiology, UIN Malang and UIN Surabaya form the character of ulul albab